Preparation and Characterization of Camelina sativa Protein Isolates and Mucilage. (31st August 2017) - Sarv, Viive; Trass, Olev; Diosady, Levente L.
Abstract: Processes for the production of protein isolates from camerlina Camelina sativa were developed by modifying the procedure used for other seeds from the Brassicaceae family, such as rapeseed and mustard. The procedure consisted of defatting the seed followed by alkaline extraction at pH 11, ultra‐ and diafiltration using a 5‐kDa membrane, isolelectric precipitation of the proteins at pH 5 and recovery of the acid soluble protein isolates (SPI) after further filtration and drying. Protein yields as precipitated protein isolate and SPI were 10.7 and 11.4%, containing 67 and 42%, respectively. Due to the high concentration of mucilage in camelina, a water‐to‐seed ratio of 30 had to be used for protein extraction from the hexane‐defatted seed and most of the mucilage had to be removed prior to the defatting process. A rapid mucilage extraction process using water at 55 °C was developed. Camelina mucilage absorbs water and oil. Viscosity measurements of dried and redissolved mucilage showed the highest values at natural pH, and the viscosity increased rapidly above 1% solids concentration. It may be a useful product in the food and pharmaceutical industries.